Éloge de la Méthode: A Tribute to Garrison Sposito on the Occasion of His Retirement - Charlet, Laurent; Baham, John; Giraldez, Juan V.; Lo, WeiCheng; Aristilde, Ludmilla; Baveye, Philippe C. (Frontiers in Environmental Science, 2016)
When confronted with a great piece of art or research, one often wonders about what made it possible, what method was used by its author, in part so one can try to emulate it in one's own activities. Upon the retirement of Garrison Sposito after a long and very distinguished career, we considered that, as former doctoral students of Gary's, we were in a privileged position to write, in our own words and from our perspective, an account of the various key ingredients of his very successful "method." In the following, we identify and review six components of this method, respectively his thorough bibliographical coverage, extreme rigor in research, meticulous crafting of manuscripts, parallel focus on several disciplines, firm conviction that it is not necessary to go out of one's way to promote good ideas or competent people, and finally his reluctance to jump on bandwagons. We hope that this analysis of the pillars of Gary's method, at least as we see them, will not only help pay tribute to an outstanding thinker, but also inspire and provide a roadmap to all those who strive to better themselves as researchers.